CULTURAL VALUES OF BATAK TOBA IN WEDDING CEREMONY : A STUDY OF ORAL TRADITION - Dorlina Nababan; Zainuddin Zainuddin; Muhammad Natsir (Universitas Negeri Medan, 2020)
The objectives of this studywas to find out the cultural values of Batak Toba in the wedding ceremony. The study was conducted by using textual research. The data of this study were taken from Hula-hula utterances in the wedding ceremony of Batak Toba. It was focusing on giving tradition Batak Toba cloth worn covering shoulder event (mangulosi) to the groom’s family (boru). The data were analyzed by using theory of Harahap and Siahaan (1987). There were nine cultural values found in the wedding ceremony. They were kinship, religion, extended family, respect, wealth, modernization, justice, nurture, and conflict.